2017
DOI: 10.1053/j.gastro.2017.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Patient Age, Sex, and Inflammatory Bowel Disease Phenotype Associate With Course of Primary Sclerosing Cholangitis

Abstract: BACKGROUND & AIMS Primary sclerosing cholangitis (PSC) is an orphan hepatobiliary disorder associated with inflammatory bowel disease (IBD). We aimed to estimate the risk of disease progression based on distinct clinical phenotypes in a large international cohort of patients with PSC. METHODS We performed a retrospective outcome analysis of patients diagnosed with PSC from 1980 through 2010 at 37 centers in Europe, North America, and Australia. For each patient, we collected data on sex, clinician-reported a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
442
9
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 404 publications
(483 citation statements)
references
References 67 publications
16
442
9
16
Order By: Relevance
“…40 These observations were recently confirmed in a large retrospective outcome analysis. 41 Recent results of genetic studies identify PSC-IBD as a single entity, and future work should address whether there are any differences in the immune response associated with colitis in PSC-CD vs PSC-UC.…”
Section: Discussionmentioning
confidence: 98%
“…40 These observations were recently confirmed in a large retrospective outcome analysis. 41 Recent results of genetic studies identify PSC-IBD as a single entity, and future work should address whether there are any differences in the immune response associated with colitis in PSC-CD vs PSC-UC.…”
Section: Discussionmentioning
confidence: 98%
“…However, a recent article reported that clinically progressive PSC requiring LT is associated with milder UC disease activity, including less use of steroids, azathioprine, and need for surgery . Moreover, in a recent cohort of >7,000 PSC patients, concurrent Crohn's disease or no IBD were associated with a lower risk of LT or death compared to UC …”
Section: Scope Of the Problemmentioning
confidence: 99%
“…1 There is no medical treatment available and patients have an increased risk of both hepatobiliary and bowel malignancies. 4 The pathogenesis is still unclear, although a dysregulated immune reaction at the epithelial barrier in the intestine and the biliary system may play a key role. 4 The pathogenesis is still unclear, although a dysregulated immune reaction at the epithelial barrier in the intestine and the biliary system may play a key role.…”
Section: Introductionmentioning
confidence: 99%